Sampling and randomisation in experimental and quasi-experimental CALL studies: Issues and recommendations for design, reporting, review, and interpretation. - Ballance O (Cambridge University Press on behalf of EUROCALL, the European Association for Computer-Assisted Language Learning, 2024)
The majority of research papers in computer-assisted language learning (CALL) report on primarily quantitative studies measuring the effectiveness of pedagogical interventions in relation to language learning outcomes. These studies are frequently referred to in the literature as experiments, although this designation is often incorrect because of the approach to sampling that has been used. This methodological discussion paper provides a broad overview of the current CALL literature, examining reported trends in the field that relate to experimental research and the recommendations made for improving practice. It finds that little attention is given to sampling, even in review articles. This indicates that sampling problems are widespread and that there may be limited awareness of the role of formal sampling procedures in experimental reasoning. The paper then reviews the roles of two key aspects of sampling in experiments: random selection of participants and random assignation of participants to control and experimental conditions. The corresponding differences between experimental and quasi-experimental studies are discussed, along with the implications for interpreting a study’s results. Acknowledging that genuine experimental sampling procedures will not be possible for many CALL researchers, the final section of the paper presents practical recommendations for improved design, reporting, review, and interpretation of quasi-experimental studies in the field.
Keywords: research methodology; computer-assisted language learning; CALL; sampling; experimental design; quasiexperimental design